2019
DOI: 10.1177/1464419319879790
|View full text |Cite
|
Sign up to set email alerts
|

A new vertical dynamic model for railway vehicle with passenger-train-track coupling vibration

Abstract: In order to further reveal the vertical random vibration characteristics of railway vehicles, using the system engineering method, taking the passenger, the train system, and the track system (ballast track) as a unified whole, a passenger-train-track vertical coupling dynamic model is established, and the vibration differential equations of the model are derived. In the model, passengers are regarded as a single-degree-of-freedom system attached to the bottom of the carriage, the train system is represented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…), and these are mainly evaluated on acting forces, velocities and accelerations, as well as other quantities. They use various ways and methods of analysing and evaluating dynamical effects and running properties [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…), and these are mainly evaluated on acting forces, velocities and accelerations, as well as other quantities. They use various ways and methods of analysing and evaluating dynamical effects and running properties [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…1214 The hunting stability of a rail vehicle was studied using wheel-rail contact, wheel conicities, and suspension characteristics. 15,16 Furthermore, the ride comfort of tilting rail cars travelling on an irregular curving track is studied by researchers. 17,18…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] The hunting stability of a rail vehicle was studied using wheel-rail contact, wheel conicities, and suspension characteristics. 15,16 Furthermore, the ride comfort of tilting rail cars travelling on an irregular curving track is studied by researchers. 17,18 Since research on active and semi-active suspension technologies in the field of vehicle engineering continues to gain attention due to its ability to vary the suspension force as per requirement.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated experimentally and numerically that when the passengers exist on the vehicle, a large part of the peak value of acceleration PSD is canceled; therefore, they concluded that the passengers act as damper elements. Yu et al (2020) 25 proposed a comprehensive model that included passengers, vehicles, and track models to investigate the vertical vibrations of the passengers. Such works proposed different passenger body-seat dynamic models to consider the coupled flexural vibrations of the carbody and its passengers.…”
Section: Introductionmentioning
confidence: 99%